Performance of early pregnancy HbA1c for predicting gestational diabetes mellitus and adverse pregnancy outcomes in obese European women. (October 2020) - Immanuel, Jincy; Simmons, David; Desoye, Gernot; Corcoy, Rosa; Adelantado, Juan M.; Devlieger, Roland; Lapolla, Annunziata; Dalfra, Maria G.; Bertolotto, Alessandra; Harreiter, Jürgen; Wender-Ozegowska, Ewa; Zawiejska, Agnieszka; et al.
Highlights: Early pregnancy HbA1c is a poor predictor of gestational diabetes. An HbA1c ≥ 5.7% (39 mmol/mol) has poor sensitivity for GDM regardless of gestation. An HbA1c ≥ 5.7% (39 mmol/mol) was not associated with greater risk of adverse outcomes. Abstract: Aims: To investigate the performance of early pregnancy HbA1c for predicting gestational diabetes mellitus (GDM) and adverse pregnancy outcomes in obese women. Methods: Post hoc analysis using data from the Vitamin D And Lifestyle Intervention for GDM prevention trials conducted across 9 European countries (2012–2014). Pregnant women (BMI ≥ 29 kg/m 2 ) underwent a baseline HbA1c and oral glucose tolerance tests at < 20 weeks, 24–28 weeks, and 35–37 weeks. Women with GDM were referred for treatment. Results: Among the 869 women tested, the prevalence of GDM was 25.9% before 20 weeks, with a further 8.6% at 24–28 weeks. The areas under the curves for HbA1c at the two time points were 0.55 (0.50–0.59) and 0.54 (0.47–0.61), respectively. An early HbA1c ≥ 5.7% (39 mmol/mol) (N = 111) showed low sensitivity (18.2%) with 89.1% specificity for GDM before 20 weeks, at 24–28 weeks (sensitivity of 8.0% and specificity of 88.6% after excluding early GDM), and throughout gestation (sensitivity of 15.9% and specificity of 89.4%). The ≥ 5.7% (39 mmol/mol) threshold was significantly associated with concurrent GDM before 20 weeks (adjusted OR (aOR) 2.77(1.39–5.51)) and throughout gestation (aOR 1.72 (1.02–2.89)), but not adverse pregnancy outcomes. Conclusions: Early pregnancy HbA1c is of limited use for predicting either GDM or adverse outcomes in overweight/obese European women.